Designing for Adoption: A Cross-Border UB–UPM Community-Engagement Model for Small-Scale Macrobrachium rosenbergii Aquaculture - Musa, Muhammad (Journal of Innovation and Applied Technology, 2026)
The program, which aimed to operationalize fundamental husbandry concepts through skill application, involved a three-step organised training–demonstration–mentoring model and was conducted in Sungkai, Perak, Malaysia. The materials were considered to be suitable with respect to existing farm situation and would help in performance during next cycle including better FCR, SR and cost reduction. Satisfaction was high (60% scored 10), and the intent for follow-up clinic use strong (most ≥8), suggesting readiness for further capacity building. In conclusion, a short demand-driven UB–UPM collaboration model successfully developed basic competencies amongst amateur smallholder practitioners using cheaper higher controlled systems; program follow-on including post-training technical mentoring along with supervision and farm level targets are proposed in order to translate knowledge gains into verified mid-term production/ sustainability successes.